Pengembangan dan pengujian aplikasi penilaian kinerja saluran dan bangunan irigasi berbasis mobile menggunakan AppSheet (Studi Kasus: DI. Kiaraeyeuh) - Uways Muhammad Mashudi; Siegfried Syafier; Fauzia Mulyawati (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2025)
Optimal irrigation network performance is crucial to support agricultural productivity and meet the water needs of rice fields. However, the process of inventorying and assessing the condition of irrigation networks is still largely done manually, resulting in delays in reporting, potential recording errors, and low decision-making effectiveness. In accordance with the guidelines of Permen PUPR No.12/PRT/M/2015, a system is needed that is capable of evaluating the condition of irrigation assets more quickly, accurately, and in a standardized manner. This study aims to develop AsetAirKu, an AppSheet-based mobile application to support the process of inventorying and assessing the performance of irrigation channels and structures digitally, in an integrated manner, and in a way that is easy to use in the field. The research methods included a literature study on irrigation asset condition parameters, field data collection on channel profiles, sedimentation, embankment conditions, sluice gates, and other structure components, as well as the design of the application database structure. The application was developed through the stages of interface creation, data input flow, and report automation. The application was tested in the Kiaraenyeuh Irrigation Area as a case study, assessing its effectiveness during the data collection and assessment process in the field. AsetAirKu successfully integrated the data collection and assessment processes into a single platform. The field test results showed a network performance value of 70.65%, which is in the moderate category, with a moderate level of damage and recommendations for periodic maintenance. The application is capable of accelerating data recording, improving assessment accuracy, and generating reports automatically. The main constraint of the application is its dependence on an internet connection for data synchronization and report downloading. AsetAirKu has proven to be effective as a digital tool in assessing irrigation network performance, improving reporting efficiency, and supporting data-driven decision making.